Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Section 11.1 - Solving Quadratic Equations by Completing the Square - Exercise Set - Page 767: 98


b = 6 and b = -6

Work Step by Step

In a perfect square trinomial, in th form $ax^{2} + bx + c$, the constant (c) is equal to the square of half the coefficient of the second term, b. $c = (\frac{b}{2})^{2}$ Substitute c with 9 and solve for b. $9= (\frac{b}{2})^{2}$ To undo the square, we need to take the square root of 9, which will equal to either positive 3 or negative 3. In this case, we will split this off into two equations to solve for the two possible values for the second term coefficient. $3 = \frac{b}{2} $ and $ -3 = \frac{b}{2}$ Solve for b by multiplying both sides of the equation by 2. b = 6 and b = -6
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.